1995
DOI: 10.1128/mcb.15.3.1254
|View full text |Cite
|
Sign up to set email alerts
|

The Embryonic Enhancer-Binding Protein SSAP Contains a Novel DNA-Binding Domain Which Has Homology to Several RNA-Binding Proteins

Abstract: Stage-specific activator protein (SSAP) is a 43-kDa polypeptide that binds to an enhancer element of the sea urchin late histone H1 gene. This enhancer element mediates the transcriptional activation of the late histone H1 gene in a temporally specific manner at the mid-blastula stage of embryogenesis. We have cloned cDNAs encoding SSAP by using polyclonal antibodies raised against purified SSAP to screen expression libraries. SSAP is unrelated to previously characterized transcription factors; however, it exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 60 publications
2
46
1
Order By: Relevance
“…RRMs are found in many RNA-binding proteins, including translation factors, poly(A)-binding proteins, and proteins associated with pre-mRNA and pre-rRNA processing (51). This domain has also been found in DNA-binding proteins and can be involved in protein-protein interactions (52)(53)(54).…”
Section: Resultsmentioning
confidence: 99%
“…RRMs are found in many RNA-binding proteins, including translation factors, poly(A)-binding proteins, and proteins associated with pre-mRNA and pre-rRNA processing (51). This domain has also been found in DNA-binding proteins and can be involved in protein-protein interactions (52)(53)(54).…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, both EhEBP1 and EhEBP2 contained regions of homology to the RNA recognition motif (RRM), a nucleotide binding motif found in a large group of RNA-binding proteins (24,25). The RRM is also present in several sequence-specific DNA-binding proteins, such as stage-specific activator protein (SSAP) (26). EhEBP1 contained two full copies of the RRM as well as a 54-amino acid region with many acidic and basic residues (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The DNA recognition sites for both of these proteins are AT-rich, and both proteins show sequence-specific binding to both singlestranded and double-stranded DNA. It has been suggested that these AT-rich sites exhibit some single-stranded character in the cell, allowing for interaction between the conserved aromatic residues within the ␤ sheets of the RRM and nucleotides in the recognition site (26). Interestingly, the URE4 motif recognized by EhEBP1 and EhEBP2 is also AT-rich, which might pose problems for sequence-specific recognition in the context of the AT-rich E. histolytica genome.…”
Section: Figmentioning
confidence: 99%
“…Interestingly, in parallel to this work it was shown that HBsu, the HU protein of Bacillus subtilis, specifically binds the Alu domain of a small cytoplasmic RNA (scRNA), a homologue of mammalian signal recognition particle RNA (24). In the eukaryotic field, a growing body of evidence shows that a number of proteins including transcriptional factors containing zinc finger or RNA recognition motifs are able to bind specifically to both DNA and RNA (25)(26)(27)(28)(29)(30)(31)(32)(33).…”
mentioning
confidence: 97%